PERAN PEMBIAYAAN ISTISHNA DALAM MENINGKATKAN KINERJA KEUANGAN (ROA) PADA BANK UMUM SYARIAH - iswandi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This research aims to determine the percentage magnitude of the influence of istishna financing role partially on financial performance (ROA) in Sharia Commercial Banks. The data source of this research is secondary data. This type of research data is quantitative data. Secondary data were obtained through Sharia Banking Statistics obtained through Financial Services Authority (OJK) data from 14 Sharia Commercial Banks. The sample in this research were 55 (n = 55). The data analysis used is simple regression analysis, significance test (F statistical test), partial test (t statistical test) with a significance level of 5% (α = 0.05), correlation coefficient and determination test which are processed with the help of the SPSS Version 24. The results of this research indicate the Partial Role of Istishna Financing on Financial Performance (ROA) at Sharia Commercial Banks shows a positive relationship with a strong and significant correlation. The ability of the Istishna Financing variable to influence the fluctuating variations of Financial Performance (ROA) in Sharia Commercial Banks is 82.6% while the remaining 17.4% is influenced by other variables not examined in this research.